Maternal obesity in low-resource settings: a multicenter cohort study of labor and neonatal outcomes in Guinea - Diallo, Abdourahamane; Bah, Elhadj Mamoudou; Bah, Ibrahima Koussy; Sy, Telly; Hounga, Lothaire Ayadjenou; Corbaz, Fiona; Desseauve, David (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to evaluate the impact of maternal obesity on obstetrical outcomes, including labor and delivery parameters, as well as maternal and neonatal prognosis.Study designThis observational multicenter cohort study was conducted over 6 months in Conakry, where Guinea’s two busiest maternity hospitals are located. A total of 295 obese women (body mass index (BMI) > 30 kg/m2) and 590 normal-weight women (BMI 18.5–24.9 kg/m2) were included. Obstetrical characteristics and outcomes were compared between obese and normal-weight parturients.ResultsCompared to normal-weight women, obese parturients had significantly higher risks of labor induction (RR = 1.6, 95% CI [1.1–2.3]), occipital-posterior fetal position (RR = 1.8, 95% CI [1.3–2.8]), prolonged second stage of labor (RR = 1.7, 95% CI [1.2–2.3]), and oxytocin administration for uterine hypo-contractility (RR = 1.8, 95% CI [1.3–2.4]). Increased rates were also observed for episiotomy (RR = 2.5, 95% CI [1.6–3.9]), vacuum-assisted delivery (RR = 1.9, 95% CI [1.1–3.6]), cesarean section (RR = 1.7, 95% CI [1.3–4.4]), postpartum hemorrhage (RR = 1.8, 95% CI [1.3–5.2]), and postcesarean wound infection (RR = 3.3, 95% CI [2.2–19.6]). Neonates born to obese women were at an increased risk of perinatal asphyxia (RR = 2.9, 95% CI [1.3–6.4]), low APGAR score both at 1 min (RR = 1.7, 95% CI [1.3–2.2]) and 10 min (RR = 1.7, 95% CI [1.2–2.5]), and the need for neonatal resuscitation (RR = 1.6, 95% CI [1.2–2.1]). No significant differences were observed between groups regarding the risk of breech presentation, the type of cephalic presentation (occipital-anterior versus occipital-posterior), or neonatal mortality.ConclusionIn low-income settings, maternal obesity is associated with a significantly increased risk of adverse labor, delivery, and perinatal outcomes—mirroring patterns observed in higher-resource contexts. These findings underscore the need for enhanced healthcare provider training and the implementation of targeted maternal weight management strategies. Moreover, obstetrical protocols and clinical guidelines should be adapted based on maternal BMI to better address the specific risks associated with obesity in pregnancy.